Sociobehavioral and community predictors of unsuppressed HIV viral load: multilevel results from a hyperendemic rural South African population - Tomita, Andrew; Bärnighausen, Till (AIDS <London>, 2019)
Objective:Extensive antiretroviral therapy scale-up is expected to prevent onward transmission of HIV by reducing the overall community viral load. Despite multiple studies about predictors of detectable viral load derived from clinical setting, to date, no study has established such predictors usin
Gesehen am 15.04.2020